PELAKSANAAN AUDIT OPERASIONAL DALAM PEMERIKSAAN BIDANG DANA DAN KAS PADA BANK PD. BPR. ROKAN HULU - Susanti; Nurhayati (Program Studi Akuntansi Universitas Pasir Pengaraian, 2022)
This research was conducted with the aim of knowing how the implementation of operational audits applied by Bank PD. BPR Rokan Hulu Pasir Pengaraian as the result of interpretation of SPFAIB and to determine the role of operational audit in increasing the effectiveness of teller, deposit and savings activities at Bank PD. BPR Rokan Hulu Pasir Pengaraian. This study uses a case study approach with a descriptive method that describes how the operational audit is carried out at Bank PD. BPR Rokan Hulu Pasir Pengaraian. The data used are primary data in the form of interviews with internal auditors of funds and cash, and other related sections and secondary data, namely human resources for employees obtained from the funds and cash section.The results of the study indicate that the operational audit implementation has been adequate where the operational audit has followed the minimum standards set by Bank Indonesia which of course is adjusted to the bank's business scope. Operational audit has played a significant role in increasing the effectiveness of teller, time deposit and savings activities.